1998
DOI: 10.1590/s0100-879x1998000700013
|View full text |Cite
|
Sign up to set email alerts
|

Variations in gastric emptying of liquid elicited by acute blood volume changes in awake rats

Abstract: We have observed that acute blood volume expansion increases the gastroduodenal resistance to the flow of liquid in anesthetized dogs, while retraction decreases it (Santos et al. (1991) Acta Physiologica Scandinavica, 143: 261-269). This study evaluates the effect of blood volume expansion and retraction on the gastric emptying of liquid in awake rats using a modification of the technique of Scarpignato (1980) (Archives Internationales de Pharmacodynamie et de Therapie,. Male Wistar rats (180-200 g) were fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This BV overload protocol has been extensively utilized in our previous studies, both in anaesthetized rats and in awake rats 6 . 8 –10 For investigating neural mechanisms, separate groups of rats were previously submitted to a drug pretreatment or a surgical procedure. In all protocols, the animals were killed at a fixed time interval (10 min) after liquid meal gavage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This BV overload protocol has been extensively utilized in our previous studies, both in anaesthetized rats and in awake rats 6 . 8 –10 For investigating neural mechanisms, separate groups of rats were previously submitted to a drug pretreatment or a surgical procedure. In all protocols, the animals were killed at a fixed time interval (10 min) after liquid meal gavage.…”
Section: Methodsmentioning
confidence: 99%
“…The gut seems to react to acute blood volume (BV) imbalances by adjusting the gastrointestinal (GI) motility 1 –10 as well as its permeability to fluid and electrolytes 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we have shown that blood volume redistribution modifies gastrointestinal motor behavior (14,40). Taken together, our hypothesis is that the opening of an AV fistula impels the circulation to a hyperkinetic status, which affects the gut motor behavior in virtue of hemodynamic adjustments and multiple neurohumoral changes.…”
mentioning
confidence: 66%
“…However, this effect was short-lived compared to the delay of intestinal transit, which persisted for at least 50 min after drug administration. Thus, it seems that the sildenafil-induced delay of the intestinal transit results from a direct action of the drug on the gastrointestinal smooth muscle cells, instead of a secondary hemodynamic effect (19). Interestingly, there was almost no retention of the isotope marker in the gastroduodenal stumps of the sildenafil-treated rats.…”
mentioning
confidence: 90%